Binding of haptoglobin, inter-alpha-trypsin inhibitor, and alpha 1 proteinase inhibitor to synovial fluid hyaluronate and the influence of these proteins on its degradation by oxygen derived free radicals. Issue 5 (May 1988) - Hutadilok, N; Ghosh, P; Brooks, P M
Abstract : Synovial fluid from 201 normal and pathological knee joints was subjected to gel filtration by Sepharose CL-2B chromatography to separate hyaluronic acid (HA) from unbound proteins, which were retarded on this column. HA from all normal fluids was excluded from the gel and contained 1% or less bound protein. Synovial fluids taken from joints of patients with rheumatoid arthritis (RA) contained considerably more protein bound to HA. In 46% of RA samples the level of protein was greater than 4%, whereas only one fluid examined from osteoarthritic joints contained this amount. The proteins bound to HA from RA joints were identified by sodium dodecyl sulphate/polyacrylamide gel electrophoresis (SDS-PAGE) and immunodiffusion techniques as the acute phase proteins alpha 1 proteinase inhibitor, inter-alpha-trypsin inhibitor, and haptoglobin. The average relative percentages of these proteins bound to HA were 17.6%, 32.6%, and 29.2% respectively. These HA-protein complexes could be generated in vitro by mixing normal (low protein) HA with any one of the three acute phase proteins. The HA-protein complexes formed in vitro with inter-alpha-trypsin inhibitor or haptoglobin, and those isolated from RA synovial fluids, were more resistant to degradation by oxygen derived free radicals (ODFR) than HA from normal fluids. From these findings we conclude that certain acute phase proteins diffusing into synovial fluid during inflammatory episodes may play an important part in protecting HA from depolymerisation by activated phagocytes.